Labour Market Participation and Atypical Employment over the Life Cycle: A Cohort Analysis for Germany - Ronald Bachmann; Rahel Felder; Marcus Tamm (Institute of Labor Economics (IZA), 2018)
We use data from the adult cohort of the National Education Panel Study to analyse the changes in the employment histories of cohorts born after World War II and the role of atypical employment in this context. Younger cohorts are characterised by acquiring more education, by entering into employment at a higher age, and by experiencing atypical employment more often. The latter is associated with much higher employment of women for younger cohorts. A sequence analysis of employment trajectories illustrates the opportunities and risks of atypical employment: The proportion of individuals whose entry into the labour market is almost exclusively characterised by atypical employment rises significantly across the cohorts. Moreover, a substantial part of the increase in atypical employment is due to the increased participation of women, with part-time jobs or mini-jobs playing an important role in re-entering the labour market after career breaks.
Keywords: J21; J42; J81; 330; atypical employment; regular employment; cohort differences; life cycle analysis; sequence analysis